Estudo da variação de pH interfacial durante a reação de desprendimento de hidrogênio por simulação de elementos finitos - Carneiro Neto, Evaldo Batista (2012)
Different papers propose a interfacial pH variation during an electrochemical reaction. Among them, as example, can be cited the electrodeposition of Zn and Co as well as the steel corrosion in aqueous sulphide solutions. Considering this, we decide to investigated from a fundamental point of view such interfacial pH change during Hydrogen Evolution Reaction using finite elements method. The need to use numerical methods is related to the coupling among a large number of differential equations which have not any analytical solution under those conditions generally used in an electrochemical measurement. To perform such task we used Comsol Multiphysics software under Linux (Ubuntu 10.04). As the main purpose, we want to understand the pH change phenomena and explore also where it truly occurs during a reduction reaction. To investigate the system, it was simulated both, Volmer-Tafel and Volmer-Heyrovský mechanism and also considering both the hydronium and water reduction reactions. The transport of both H3O+ and OH- were described using the Nernst-Planck equation considering the diffusion and, in some cases, the conveccion. The charge transference for the produced/consumed species were modelled using the Butler-Volmer equation. It was also described the water dissociation and hydronium/hydroxil recombination reaction constant during the simulation experiments. Finally, the adsorption of H atoms on the surface we considered using Langmuir adsorption isotherm. Two different kinds of experiment were described under unidimensional geometry: linear sweep voltammetry and chronopotentiometry curves. 2-D geometry was used to simulate the ring-disk electrodes and also microelectrodes which were investigated in constant potential and voltammetric transients. The results shown that depending on the multiple variables presented above an interfacial pH change up 4.2 units can occur which surely modifies in a transient form the experimental conditions and must be considered during the design of such experiments.